Exaggerated elastin turnover in childhood and adolescence in Marfan syndrome – correlation with age – new insights from the AIMS trial. (14th October 2021) - Iskandar, Z; Dodd, M; Stuart, G; Caputo, M; Clayton, T; Chin, C; Gibb, J; Child, A; Jin, X Y; Flather, M; Huang, J T J; Choy, A M
Abstract: Background: Marfan syndrome (MFS) is an autosomal dominant connective tissue disorder caused by mutations in the Fibrillin1 gene (FBN1) that leads to impaired elastin formation and extra-cellular matrix homeostasis. Elastin synthesis and related lamellae formation in the aorta is completed in the newborn. Thereafter further elastin turnover is thought to be minimal during life. Elastin homeostasis is little studied in patients with MFS who have been reported to have reduced elastin in their aorta and are at risk of aortic dilatation and consequent life-threatening dissection. It is not clear if elastin loss is due to reduced elastin formation in utero or accelerated degradation during life. However, aortopathy develops early in MFS with 70% of patients developing aortic dilatation by the age of 20 years. Therefore, the longitudinal and circumferential aortic growth that occurs in childhood may involve elastic lamellae remodelling that is impaired in MFS. Desmosine is the cross-link component in the elastin molecule and is exclusively released from mature elastin breakdown, thus is a physiologically relevant biomarker of elastin turnover. We hypothesise that physiologic aortic growth is associated with elastic lamellae remodelling and increased elastin turnover, detected by elevated plasma desmosine (pDES), and that elastin turnover is exaggerated during the fast-growing period in MFS. Purpose: The aims of this study were 1. To investigate the relationship between elastin turnover and age in the control subjects, and 2. To compare the elastin turnover in MFS with control subjects. Methods: pDES was measured by stable isotope dilution LC-MS/MS in 113 MFS subjects (48% male, mean age 18.2±9.4 (SD) years), mean aortic root 33.8±2.1mm and Z-score 3.4±2.1 in the AIMS trial at baseline before intervention, and in 109 healthy controls (46% male, mean age 26.1±9.5 years). Results: pDES levels were associated positively with age, body surface area and negatively with diastolic BP in the control group (p=0.05 and 0.21 respectively after correcting for age). In MFS subjects pDES also positively correlated with age and male sex (p<0.05). Interestingly, the age-dependent association with pDES showed a peak distribution in both control and MFS groups (Figure 1) where teenage children expressed the highest pDES levels. MFS subjects had significantly higher pDES compared to controls before the age of 20 (p=0.01) but in adulthood, there was no difference (Figure 2). Conclusion: Elastin turnover is highly dynamic before early adulthood, and peaks in adolescence and is exaggerated in MFS, suggesting that this period of growth is critical in developing aortopathy. FUNDunding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): British Heart FoundationTENOVUS Scotland